Analisis Konflik Batin Tokoh Utama dalam Novel “Namaku Alam” Karya Leila S. Chudori - Sanjaya, Puja Rakes; Zasrianita, Fera; Sari, Wenny Aulia (LITERATUR: Jurnal Bahasa, Sastra dan Pengajaran, 2024)
ABSTRACT This study aims to describe the forms of internal conflict experienced by the main character in the novel "“Namaku Alam”" by Leila S. Chudori. Utilizing a library research method, the researcher collected data by thoroughly reading and analyzing the novel and relevant literature. The findings indicate the presence of 12 forms of internal conflict, including depression, obsession, anxiety, fear, insecurity, guilt, incapacity, frustration, anger, heartache, dissatisfaction, and attention, comprising a total of 129 data points. Each conflict is characterized by specific emotional responses and psychological manifestations, revealing the complex nature of the protagonist's struggles. The study concludes that the depiction of these internal conflicts reflects the profound psychological turmoil faced by individuals in a socio-political context, thus emphasizing the significance of psychological analysis in literary studies. Keywords: Internal Conflict, My Name is Alam, Novel